Cardiovascular health monitoring in patients with psychotic illnesses: A project to investigate and improve performance in primary and secondary care. Issue 1 (19th March 2013) - Modi, Rakesh Narendra; Ledingham, David
Abstract: Patients with psychotic illnesses are predicted to die 15 years younger than the national average. The chief cause is cardiovascular disease (1). Evidence-based guidelines including those produced by the National Institute of Health and clinical Excellence and the Quality Outcomes Framework, recommend regular monitoring of their cardiovascular risk (2, 3, 4). Primary health care audits were undertaken in an urban and a rural setting. These looked at the proportion of patients who had their physical health regularly monitored in line with NICE guidelines. Following an audit in general practice, it became clear that there was a group of patients that were chronic non-attenders. It was not clear whether these patients were the responsibility of the general practices or psychiatric services. An audit in secondary care then looked at the level of cardiovascular health monitoring in that setting, and the communication of results to primary care. These audits demonstrated that monitoring of cardiovascular health did not meet standards as set by NICE. Further to this, communication of findings between primary and secondary care was also poor. Primary care interventions included setting up Alert reminder boxes on the computer system and sending invitations for clinic attendance to 'at risk' patients. In secondary care interventions included redesign of the patient lists to include a way of monitoring cardiovascular health and generation of a new discharge summary to facilitate communication of cardiovascular indicators to primary care. These interventions have resulted in marked improvements in cardiovascular health monitoring in primary care, however, there is still room for considerable improvement. Discussions about further intervention strategies, and further audit cycles, are ongoing.